Clinical Report of Probable Catastrophic Antiphospholipid Syndrome in Pregnancy - Eryk Hakman; Sasha Mikhael (Case Reports in Obstetrics and Gynecology)
Background. Catastrophic APS (CAPS) is a rare but life-threatening form of APS defined as multiorgan thrombosis affecting a minimum of three organs with confirmation by histopathology of small vessel occlusions in at least one organ or tissue. The development of CAPS in pregnancy poses many diagnostic challenges as a result of its broad range of clinical presentations and its overlap with other obstetric complications and microangiopathic diseases. Because of the high associated mortality rate, prompt recognition and treatment are paramount. Case. A twenty-five-year-old G3P0111 with a history of multiple thromboembolisms presented at 21 weeks and 3 days of gestation with complaints of right upper quadrant pain, visual disturbances, headache, and syncopal episodes. Laboratory evaluation demonstrated microangiopathic disease with hemolysis (confirmed on peripheral smear), elevated liver enzymes, and abnormal 24-hour urine protein with vital signs within the normal range. Presence of significantly elevated antiphospholipid antibodies was noted, facilitating the diagnosis of probable CAPS. Proper workup was achieved based on clinical suspicion, allowing immediate and appropriate management. Conclusion. CAPS is a life-threatening condition rarely seen in pregnancy making early recognition difficult. A low threshold to initiate urgent and aggressive treatment should be maintained to minimize the risk of adverse outcomes.